Endogenous CCN family member WISP1 inhibits trauma-induced heterotopic ossification - Hsu, Ginny Ching-Yun (JCI Insight, 2020)
Heterotopic ossification (HO) is defined as abnormal differentiation of local stromal cells of mesenchymal origin, resulting in pathologic cartilage and bone matrix deposition. Cyr61, CTGF, Nov (CCN) family members are matricellular proteins that have diverse regulatory functions on cell proliferation and differentiation, including the regulation of chondrogenesis. However, little is known regarding CCN family member expression or function in HO. Here, a combination of bulk and single-cell RNA sequencing defined the dynamic temporospatial pattern of CCN family member induction within a mouse model of trauma-induced HO. Among CCN family proteins, Wisp1 (also known as Ccn4) was most upregulated during the evolution of HO, and Wisp1 expression corresponded with chondrogenic gene profile. Immunohistochemistry confirmed WISP1 expression across traumatic and genetic HO mouse models as well as in human HO samples. Transgenic Wisp1(LacZ/LacZ) knockin animals showed an increase in endochondral ossification in HO after trauma. Finally, the transcriptome of Wisp1-null tenocytes revealed enrichment in signaling pathways, such as the STAT3 and PCP signaling pathways, that may explain increased HO in the context of Wisp1 deficiency. In sum, CCN family members, and in particular Wisp1, are spatiotemporally associated with and negatively regulate trauma-induced HO formation.